Neuroscience Theories, Hypothesis and Approaches to ASD Physiopathology. A Review - Castejón OJ (Journal of Neurological Research And Therapy, 2019)
According to the results of our laboratory the theory of immune dysfunction, the theory on the genetic architecture of ASD, the disrupted cortical connectivity theory and the theory on the contribution of cerebellum to ASD have shown fundamental experimental evidences to support the core symptoms of the complex and enigmatic physiopathology of autism spectrum disorder. The additional hypothesis about the neurogenesis in the amygdala, the contribution of oxytocin, vasopressin, the mirror neuron network, and mitochondrial dysfunction described are stimulating and interesting approaches that deserve further systematic basic and clinical neuroscience research.
Keywords: autism